Iron (Fe) Content in Community Well Water around Mabar Hilir Industrial Area Market 3 Bantenan Medan City in the Perspective of Health and Islamic - Yulia Khairina Ashar; Nuraisyah Wulandari Panjaitan; M. Iqbal; Hazra Imron (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Community well water that contains excessive iron (Fe) can have a negative effect on humans who come in contact with or consume the well water, which can irritate the eyes, skin and also cause liver cancer. The purpose of this study was to determine the iron content in community well water around the Mabar Hilir Industrial Area Pasar 3 Bantenan, Medan City. This was an observational research with cross sectional design. The population of this study is the community well water, the number of samples were 10 wells. Sampling was done by purposive sampling and to determine the content of iron (Fe) in well water, samples were taken for testing in the laboratory using the APHA 3120B, 22 nd ed.2012 method. The data analysis used was univariate data analysis. The results of this research showed that it can be seen that out of 10 wells, there are 2 wells that do not qualify as drinking water, namely wells 8 and 9 with the amount of iron content in the well water is 1.913907 and 0.73374 respectively (quality standard = 0.3 mg/L) and 1 well that does not qualify as clean water, namely well 8 with the amount of iron content in the well water is 1.913907 (quality standard = 1.0 mg/L). The drinking water quality standard is based on the regulation of the Indonesian Minister of Health No. 492/Menkes/Per/IV/2010 where the maximum allowable iron (Fe) content is 0.3 mg/L. Clean water quality standard based on the regulation of the Indonesian Minister of Health No. 32 Year 2017 where the maximum allowable iron (Fe) content is 1.0 mg/L.Keyword: Iron (Fe), Industry, Quality Standard, Water.